The rejection of religious nationalism towards the secular state and the Islamic caliphate: Indonesian religious figures perspective - Imam Sutomo; Budihardjo Budihardjo (Indonesian Journal of Islam and Muslim Societies, 2021)
Religious nationalism is interpreted differently in its application in various countries. The purpose of this study is to explore the development of the meaning of religious nationalism values according to religious figures in Indonesia. The research method used to analyze social phenomena is a qualitative approach, using direct interviews and observations as the main data collection instruments. The essential results of this study are the values of religious nationalism must be preserved as a binder of social harmony since the formation of the Indonesian state. Religious figures view that the values of religious nationalism in Indonesia reject the secular state and the idea of an Islamic state (caliphate). The critical implication of this research is that religious figures promote the implementation of universal religious values in the public sphere and urge freedom of expression of religious activities democratically without discrimination for adherents of all religions.